Exposure to substance and current substance among school-going adolescents in Timor-Leste - Adade, A.E.; Ansah, K.O.; Dey, N.E.Y.; Arthur-Holmes, F.; Duah, H.O.; Pascal, A. (PLOS Global Public Health, 2022)
Few studies have examined how exposure to substance influences adolescent’s use of substance in Timor-Leste. We assessed this relationship using nationally representative data from Timor-Leste to address this gap. Data was pulled from the 2015 Timor-Leste Global school-based student health survey. Data of students aged 13-17years (N = 3700) from class 7–11 across schools in Timor-Leste were analyzed for this study. Second-hand smoking exposure (AOR = 1.57 [1.31, 1.89] and parental tobacco use, AOR = 1.94 [1.54, 2.44]) was significantly related to in-school adolescent’s current use of substance after adjusting for covariates. Current substance use was also positively associated with being male, being in class 10–12, and being food insecure and negatively associated with having at least three close friends and benefiting from parental supervision. To reduce substance use among inschool adolescents, policymakers must consider the inclusion of all models in the social learning environment of adolescents in Timor-Leste.
Research Article
Keywords: Exposure; substance; school-going adolescents; Timor-Leste